Maximising effectiveness of talent pools through mindfulness: An empirical investigation in a multinational corporation - TARMO RAUDSEPP (Institutional Knowledge at Singapore Management University, 2023)
Traditional human resource management is looking to identify and develop talent for maximising human capital in a competitive environment with limited resources and negative demographic trends. Attracting, deploying, motivating, developing and retaining talented employees is a corporate norm for meeting organisational goals. Proper human resource processes through rigorous mapping of employees according to the performance-potential matrix allow the grading of employees against peer groups to establish talent pools for development and internal succession planning. Mindfulness originates from 2,500-year-old Buddhist spiritual practices and has a rare combination of spirituality and science. Eastern perspective originates from Asian traditions focusing on the self-regulation of emotions for improving well-being. Western perspective has developed during the last 50 years in clinical psychology practices and organisational behaviour studies as a present-centred awareness-acceptance model for reducing stress, strengthening emotional intelligence and enabling strategic thinking. The mindfulness concept has moved from psychology and organisational behaviour studies to leadership development programs. Latest cutting-edge leadership development programs see the mastery of mindfulness only as the first step for increasing leadership capabilities and improving employee performance and job satisfaction. The current study offers new insights into mindfulness's role in talent management, demonstrating that a higher capacity of consciousness leads to improved talent depth and breadth. The findings indicate compensation mechanisms between mindfulness facets while proving that a high level of both awareness and acceptance is needed to become part of the talent pool for accelerated growth. Evidence also suggests that supervisor mindfulness is essential in unlocking employee talent potential through improving employee mindfulness and proposes a "Winning Mindfulness Formula in the Talent Management Process" to position organisations better in the war for talent.